Birth during on-call period: Impact of care organization on mortality and morbidity of very premature neonates - Cambonie, Gilles; Theret, Bénédicte; Badr, Maliha; Fournier, Patricia; Combes, Clémentine; Picaud, Jean-Charles; Gavotto, Arthur (Frontiers in Pediatrics, 2022)
Objectives The evidence that risks of morbidity and mortality are higher when very premature newborns are born during the on-call period is inconsistent. This study aimed to assess the impact of this situation among other determinants of outcomes, particularly newborn characteristics and care organization. Methods Observational study including all infants born < 30 weeks’ gestation in a French tertiary perinatal center between 2007 and 2020. On-call period corresponded to weekdays between 6:30 p.m. and 8:30 a.m., weekends, and public holidays. The primary endpoint was survival without severe morbidity, including grade 3–4 intraventricular hemorrhage (IVH), cystic periventricular leukomalacia, necrotizing enterocolitis, severe bronchopulmonary dysplasia (BPD), and severe retinopathy of prematurity. The relationship between admission and outcome was assessed by an adjusted odds ratio (aOR) on the propensity of being born during on-call period and expressed vs. weekday. Secondary analyses were carried out in extremely preterm newborns (<27 weeks’ gestation), in cases of early death (within 7 days), and before (2007–2013, 51.5% of the cohort) vs. after (2014–2020, 48.5% of the cohort) the implementation of a pediatrician-nurse team dedicated to newborn care in the delivery room. Results A total of 1,064 infants [27.9 (26.3; 28.9) weeks, 947 (760; 1,147) g] were included: 668 during the on-call period (63%) and 396 (37%) on weekdays. For infants born on weekdays, survival without severe morbidity was 54.5% and mortality 19.2%. During on-call, these rates were 57.3% [aOR 1.08 (0.84–1.40)] and 18.4% [aOR 0.93 (0.67–1.29)]. Comparable rates of survival without severe morbidity [aOR 1.42 (0.87–2.34)] or mortality [aOR 0.76 (0.47–1.22)] were observed in extremely preterm infants. The early death rate was 6.4% on weekdays vs. 8.2% during on-call [aOR 1.44 (0.84–2.48)]. Implementation of the dedicated team was associated with decreased rates of mortality [aOR 0.57 (0.38, 0.85)] and grade 3–4 IVH [aOR 0.48 (0.30, 0.75)], and an increased rate of severe BPD [aOR 2.16 (1.37, 3.41)], for infants born during on-call. Conclusion In this cohort, most births of very premature neonates occurred during the on-call period. A team dedicated to newborn care in the delivery room may have a favorable effect on the outcome of infants born in this situation.